2019
DOI: 10.1016/j.bios.2018.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cDNA on GMR biosensor array towards point-of-care gene expression analysis

Abstract: Gene expression analysis at the point-of-care is important for rapid disease diagnosis, but traditional techniques are limited by multiplexing capabilities, bulky equipment, and cost. We present a gene expression analysis platform using a giant magnetoresistive (GMR) biosensor array, which allows multiplexed transcript detection and quantification through cost-effective magnetic detection. In this work, we have characterized the sensitivity, dynamic range, and quantification accuracy of Polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Bunroddith and colleagues developed a QCM sensor for the ultrasensitive detection of DNA with results comparable to the ones obtained using a SPR sensor platform [8]. Ravi et al reported a rapid screening method of Ehrlichia canis PCR amplification products based on PCR assay combined with QCM [9]. Regarding RNA biosensors, Tedeschi and coworkers reported that they successfully achieved a QCM label-free RNA biosensor with high specificity, reusability, and the ability to provide quantitative information [2].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bunroddith and colleagues developed a QCM sensor for the ultrasensitive detection of DNA with results comparable to the ones obtained using a SPR sensor platform [8]. Ravi et al reported a rapid screening method of Ehrlichia canis PCR amplification products based on PCR assay combined with QCM [9]. Regarding RNA biosensors, Tedeschi and coworkers reported that they successfully achieved a QCM label-free RNA biosensor with high specificity, reusability, and the ability to provide quantitative information [2].…”
Section: Introductionmentioning
confidence: 90%
“…PNAs are DNA mimics in which the bases are attached to a neutral N-(2-aminoethyl)-glycine pseudopeptide backbone, and LNAs are nucleic acid analogues in which the ribose ring is "locked" by a methylene bridge that shows increased thermal stability [4]. Other capture probes used are chemically modified at one of the oligonucleotide ends, and usually, biotin, thiol, or amine residues are aggregated, biotin and thiol being the most used chemical modifications [7][8][9][37][38][39][40]. Moreover, the surface chemistry used in this study enabled the immobilization of cDNA, which allowed developing a biosensor for gene expression determination from children with obesity.…”
Section: Real-time Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Like the immunoassay-based GMR sensing platforms, there is also a need for pushing GMR-based genotyping toward POC applications, which requires shorter assay time, improved sensitivity, and broader dynamic range. Recently, Ravi et al reported that their GMR sensors were capable of simultaneously detecting multiple transcripts with a dynamic range of 4 orders of magnitude and a LOD of 1 pM and 0.1 pM, respectively, for 15-and 18-cycle amplified products, which demonstrated GMR biosensors' potential to be rapid and sensitive POC platforms for genotyping [125].…”
Section: Gmr-based Sensors For Genotypingmentioning
confidence: 99%
“…Recently, research on biosensors based on magnetic labels using magnetoresistance has been actively conducted for various biomedical applications [1][2][3]. Simple device configurations of magnetoresistive (MR) biosensors, combined with low noise in concentration measurements of biosamples [4,5], make MR biosensors very promising as in vitro diagnostic devices and point-of-care testing systems [6][7][8]. The largest share of recent works on magnetic biosensors considers giant magnetoresistive (GMR) sensors [9,10] and tunneling magnetoresistive (TMR) sensors [11] as the most promising sensors for biosensor applications.…”
Section: Introductionmentioning
confidence: 99%